Metal-free amidation of carboxylic acids with tertiary amines - Wong Phakhodee (2018)
© 2016 The Royal Society of Chemistry. A direct amidation of carboxylic acids with tertiary amines could be carried out in the presence of the Ph3P-I2 activator. With an appropriate reagent addition sequence, a range of carboxylic acids including aliphatic, allylic, and aromatic acids could be converted into their corresponding tertiary amides under mild conditions without requirement of metal catalysis.